Demonstrating the psychometric properties of a problem‐related distress screener in a community sample of 319 cancer survivors. Issue 6 (27th June 2012) - Miller, Melissa F.; Buzaglo, Joanne S.; Clark, Karen L.; Loscalzo, Matthew J.; Kennedy, Victoria; Taylor, Julie; Dougherty, Kasey Ryan; Golant, Mitch
Abstract Objective The purpose was to test the psychometric properties of a 36‐item community‐based problem‐related distress screening tool, among 319 cancer survivors recruited across 14 affiliates of the Cancer Support Community. Methods Internal reliability was estimated using Cronbach's alpha coefficient. Test–retest reliability was assessed using the intra‐class correlation coefficient (ICC). Concurrent validity was determined by correlations with the Functional Assessment of Cancer Therapy‐General Well‐Being Scale (FACT‐G), the Center for Epidemiologic Studies Depression Scale (CES‐D), and the Distress Thermometer (DT) and receiver operating characteristic (ROC) curve analysis using the CES‐D (≥16) and DT (≥4) as the criterion. Non‐parametric analysis of variance was used to establish discriminant validity. Results The distress screener demonstrated high internal consistency (Cronbach's alpha = 0.91) and strong test–retest reliability (ICC ≥ 0.75). Summary scores of the distress screener correlated substantially with the FACT‐G (R2 = 0.58, p < 0.001), CES‐D (R2 = 0.48, p < 0.001), and DT (R2 = 0.35, p < 0.001) indicating strong concurrent validity and were able to discriminate groups of clinical relevance. ROC analyses showed a cutoff score of 8 for problem items rated ≥3 had optimal sensitivity and specificity relative to the CES‐D and DT. Conclusions The distress screener shows strong psychometric properties and can be considered a valuable community‐based instrument to screen for psychological distress related to social, emotional, physical, and other patient‐related symptoms and problems. This study is the first to address the chasm between hospital and community‐based screening by validating a community‐based instrument and has begun to demonstrate the feasibility of screening in the community. Copyright © 2012 John Wiley & Sons, Ltd.